The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/14756366.2021.1886093
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of human intestinal epithelial cells and primary human hepatocytes to trypsin-like serine protease inhibitors with potential antiviral effect

Abstract: Human intestinal epithelial cell line-6 (HIEC-6) cells and primary human hepatocytes (PHHs) were treated with 3-amidinophenylalanine-derived inhibitors of trypsin-like serine proteases for 24 hours. It was proven that treatment with MI-1900 and MI-1907 was tolerated up to 50 lM in HIEC-6. These inhibitors did not cause elevations in extracellular H 2 O 2 levels and in the concentrations of interleukin (IL)-6 and IL-8 and did not alter occludin distribution in HIEC-6. It was also found that MI-1900 and MI-1907 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Based on a modeled complex of MI-432 in matriptase it was found that the N-terminal biphenyl group of MI-432 appeared to fit into the S3/4 pocket of matriptase making contacts to the aromatic side chains of the characteristic TMPRSS2 residue Phe99, as well as to Trp215, the latter residue is found in most trypsin-like serine proteases. Modeling of this inhibitor type in TMPRSS2 suggested a very similar binding mode [30] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on a modeled complex of MI-432 in matriptase it was found that the N-terminal biphenyl group of MI-432 appeared to fit into the S3/4 pocket of matriptase making contacts to the aromatic side chains of the characteristic TMPRSS2 residue Phe99, as well as to Trp215, the latter residue is found in most trypsin-like serine proteases. Modeling of this inhibitor type in TMPRSS2 suggested a very similar binding mode [30] .…”
Section: Discussionmentioning
confidence: 96%
“…In our previous study, we demonstrated on human intestinal epithelial cells (HIEC) and on primary human hepatocytes (PHH) that MI-1900 and its structural close analogue MI-1907 (up to 50 μM) did not affect cell viability and did not elevate inflammatory responses (e.g. IL-6 and IL-8 production) [30] . Nevertheless, disturbances of redox status of PHH were observed after MI-1900 and MI-1907 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in this study, the bioavailability of CH-derived BAPs after in vitro digestion was determined using a novel co-culture of HIEC-6/HepG2 cells rather than a Caco-2 monolayer, as the expression of a key peptide transporter PepT1 is under-expressed in Caco-2 cells and predictions of peptide bioavailability could be misleading. Previous work has confirmed that HIEC cells more accurately represent the physiological in vivo conditions of the SI compared to Caco-2 cells [22][23][24]. Further studies can adopt and standardize this HIEC-6/HepG2 co-culture method, which could be adapted to investigate the first pass effects of bioactive food components, nutraceuticals and supplements.…”
Section: Discussionmentioning
confidence: 89%
“…Despite their limitations, cell culture models continue to provide a platform to predict the bioavailability of BAPs, as animal studies often to do not correlate with human data, and human trials are long, associated with increased costs and have ethical restrictions [2]. Comparisons of cell culture models to human in vivo data generally support the use of the former to assess intestinal transport [22][23][24]. Discrepancies involving in vitro assessments of kinetics and peptide activity may occur, however, if the digestive and metabolic processes are not sufficiently considered [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation